2020
DOI: 10.3390/ijerph17072591
|View full text |Cite
|
Sign up to set email alerts
|

Is Heart Rate a Confounding Factor for Photoplethysmography Markers? A Systematic Review

Abstract: Finger photoplethysmography (PPG) waveform is blood volume change of finger microcirculation that reflects vascular function. Reflection index (RI), stiffness index (SI) and second derivative of photoplethysmogram (SDPPG) are derived from PPG waveforms proposed as cardiovascular disease (CVD) markers. Heart rate (HR) is a known factor that affects vascular function. Individual resting HR variation may affect RI, SI and SDPPG. This review aims to identify studies about the relationship between HR with RI, SI an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…For clinical applications, the lossless decrypted PPG signals could be further used to evaluate the blood pressure, arterial stiffness, compliance, and UEVD/LEVD risk levels. In this study, with the time-domain analysis, experimental results indicated that the PPG signals could be applied for PPI, PRV, RT, and RI analysis [9,46,47]. RT and RI indexes of the 40 subjects could be divided into three groups, separating the normal condition from the lower PAD/higher PAD.…”
Section: Clinical Applications With Decrypted Ppg Signals and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For clinical applications, the lossless decrypted PPG signals could be further used to evaluate the blood pressure, arterial stiffness, compliance, and UEVD/LEVD risk levels. In this study, with the time-domain analysis, experimental results indicated that the PPG signals could be applied for PPI, PRV, RT, and RI analysis [9,46,47]. RT and RI indexes of the 40 subjects could be divided into three groups, separating the normal condition from the lower PAD/higher PAD.…”
Section: Clinical Applications With Decrypted Ppg Signals and Discussionmentioning
confidence: 99%
“…The time-domain analysis in Figure 4a indicates that a PPG waveform can also be used to assess CVDs, such as SI and RI [9,46,47]. SI can be estimated by (body height/t sdn ), where t sdn is the time interval between early systolic peak and diastolic peak, which indicates the stiffness level in large arteries.…”
Section: Evaluation Of the Decryption Performances For Clinical Appli...mentioning
confidence: 99%
“…Among these methods the 2 nd derivative method is the most widely used method for DN detection in the literature [28,31,32]. This approach employs the e-peak, the third peak within the 2 nd derivative of the PPG cardiac cycle, to estimate the DN within the cardiac cycle [31]. The primary limitation of the 2 nd derivative approach is its high sensitivity to noise.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews on the application of PPG signals have been carried out. Some of them focus on the specific medical use of PPG like pulse rate [ 3 ], blood pressure [ 4 , 5 ], atrial fibrillation [ 6 , 7 ], circulatory monitoring [ 8 ], nociception [ 9 ], or on the specific placement of PPG [ 10 , 11 ], others instead focused on reviewing the way that the signal has been analyzed [ 7 , 12 , 13 , 14 , 15 , 16 ] or the type of the sensor [ 17 ]. More than a decade ago, J. Allen [ 2 ] published an interesting review about the applications PPG in clinical physiological measurement.…”
Section: Introductionmentioning
confidence: 99%